COMBINED AHP AND GIS METHOD TO ENHANCE ROAD MAINTENANCE BUGET USE (International Journal of Engineering Sciences & Management Research, 2016)
More than 7 billion US dollars are spent for the national highway system every year in Korea. Due to the budget limit it is crucial to establish an efficient road maintenance budget execution plan (RMBEP) on how and where to allocate the budget so as to maximize the nation highway system performance. For this reason we propose a methodology to find an efficient RMBEP based on GIS (Geographic Information System) and AHP (Analytic Hierarchy Process). The resultant RMBEP designates which regions must be placed a priority in the road maintenance investment problem. The proposed scheme is able to minimize the possibility of mixed personal decision in decision-making process and help road managers to make the most effective BEP based on the scientific and reliable method. AHP coupled with GIS which is a powerful combination as a rational and objective approach in a location choice problem was used to make an efficient RMBEP. First, road related variables such as traffic volume (AADT, Annual Average Daily Traffic), pavement condition (MCI, Maintenance Control Index), cut-slope density, and the safety index of cut-slope were selected as criteria for AHP analysis, and the weight for each criterion was calculated through a survey from road managers at each regional road management center. GIS layers for each criterion were constructed, and then the weighted normalized criterion maps were made for establishing the decision index through linear scale transformation. GIS overlay analysis was adopted to calculate the priority of investment. The outcome from a case study for select regions shows that the pavement condition and the safety index of cut-slope are crucial elements of the decision making from the point of view on disaster management